2011
DOI: 10.1186/1532-429x-13-s1-p14
|View full text |Cite
|
Sign up to set email alerts
|

Feature Tracking: a novel method to analyze myocardial strain: Results from the CMR strain study in healthy volunteers

Abstract: We sought to determine normal gender-specific strain values in healthy subjects using Feature Tracking (FT-MRI). Background Feature tracking (FT-MRI) is a novel MRI based method to analyze myocardial strain that is fast, simple and has potential for clinical use. Similar to echocardiographic "speckle tracking" myocardial "features" can be tracked on routine steady state free precession or gradient echo images without the need for additional tagged imaging. Methods Global and regional strains including circumfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…The results from the meta-analysis revealed that mean circumferential and longitudinal strain values of our patient collective at baseline didn't show significant differences to the values derived from healthy subjects in previously published studies [21,22,4,23,7,6] (see figure 4).…”
Section: Meta-analysiscontrasting
confidence: 43%
“…The results from the meta-analysis revealed that mean circumferential and longitudinal strain values of our patient collective at baseline didn't show significant differences to the values derived from healthy subjects in previously published studies [21,22,4,23,7,6] (see figure 4).…”
Section: Meta-analysiscontrasting
confidence: 43%
“…All analyses were performed using dedicated post-processing software (cvi42, Circle Cardiovascular Imaging, Calgary, Canada), which included a strain analysis tool based on tissue tracking [13].…”
Section: Mr Image Analysismentioning
confidence: 99%
“…Their work was based on the fact that some observational studies of left ventricular function in adults suggest that global longitudinal strain correlate with EF, and is superior to EF as a predictor of outcome. Also, Kadiyala et al[ 22 ] measured values of myocardial strain in 60 normal subjects and tabulated them for reference.…”
Section: Reference Values Of Ft-cmr For Normal and Diseased Patientsmentioning
confidence: 99%